On Social Class, Anno 2014. (December 2015) - Savage, Mike; Devine, Fiona; Cunningham, Niall; Friedman, Sam; Laurison, Daniel; Miles, Andrew; Snee, Helene; Taylor, Mark
This article responds to the critical reception of the arguments made about social class in Savage et al. (2013). It emphasises the need to disentangle different strands of debate so as not to conflate four separate issues: (a) the value of the seven class model proposed; (b) the potential of the large web survey – the Great British Class Survey (GBCS) for future research; (c) the value of Bourdieusian perspectives for re-energising class analysis; and (d) the academic and public reception to the GBCS itself. We argue that, in order to do justice to the full potential of the GBCS, we need a concept of class which does not reduce it to a technical measure of a single variable and which recognises how multiple axes of inequality can crystallise as social classes. Whilst recognising the limitations of what we are able to claim on the basis of the GBCS, we argue that the seven classes defined in Savage et al. (2013) have sociological resonance in pointing to the need to move away from a focus on class boundaries at the middle reaches of the class structure towards an analysis of the power of elite formation.